Comparative study of anther development, microsporogenesis and microgametogenesis in species of Corchorus, Heliocarpus, Luehea and Triumfetta Malvaceae: Grewioideae) from South America - Lattar, Elsa Clorinda (2014)
Anther development, microsporogenesis and microgametogenesis of six species of the genera Corchorus, Heliocarpus, Luehea and Triumfetta were analysed. The genera were found to share the following characters: ontogeny of anther wall of basic type; simultaneous microsporogenesis, resulting mainly in tetrahedral tetrads; secretory tapetum and pollen grains shed at the bicellular stage. Moreover, the characters that differentiate them are: presence of uninucleate tapetal cells in Heliocarpus and Triumfetta; binucleate cells in Corchorus and multinucleate cells in Luehea; differentiation of the thickenings of the endothecium at free microspores stage in Corchorus, Heliocarpus and Triumfetta, whereas in Luehea differentiation occurs at the mature pollen grains stage; late disintegration of sporogenous tissue cell walls in Luehea; and the presence of orbicules, absent only in Corchorus. This is the first embryological report of the Grewioideae subfamily, contributing to the characterization of the genera studied. The results are discussed in relation to the known data for the family.